The Interaction Between Timescale and Pitch Contour at Pre-attentive Processing of Frequency-Modulated Sweeps - Hsieh, I-Hui; Yeh, Wan-Ting (Frontiers in Psychology, 2021)
Speech comprehension across languages depends on encoding the pitch variations in frequency-modulated (FM) sweeps at different timescales and frequency ranges. While timescale and spectral contour of FM sweeps play important roles in differentiating acoustic speech units, relatively little work has been done to understand the interaction between the two acoustic dimensions at early cortical processing. An auditory oddball paradigm was employed to examine the interaction of timescale and pitch contour at pre-attentive processing of FM sweeps. Event-related potentials to frequency sweeps that vary in linguistically relevant pitch contour (fundamental frequency F0 vs. first formant frequency F1) and timescale (local vs. global) in Mandarin Chinese were recorded. Mismatch negativities (MMNs) were elicited by all types of sweep deviants. For local timescale, FM sweeps with F0 contours yielded larger MMN amplitudes than F1 contours. A reversed MMN amplitude pattern was obtained with respect to F0/F1 contours for global timescale stimuli. An interhemispheric asymmetry of MMN topography was observed corresponding to local and global-timescale contours. Falling but not rising frequency-sweep contours elicited right hemispheric dominance. Results showed that timescale and pitch contour interacts with each other in pre-attentive auditory processing of FM sweeps. Findings suggest that FM sweeps, a type of non-speech signal, is processed at an early stage with reference to its linguistic function. That the dynamic interaction between timescale and spectral pattern is processed during early cortical processing of non-speech frequency-sweep signal may be critical to facilitate speech encoding at a later stage.